2020
DOI: 10.1002/nau.24388
|View full text |Cite
|
Sign up to set email alerts
|

Urethral bulking with Bulkamid: An analysis of efficacy, safety profile, and predictors of functional outcomes in a single‐center cohort

Abstract: Aims The aim of the present work is to analyze the safety profile, effectiveness, and favorable and unfavorable predictors of clinical outcome in urethral bulking with Bulkamid, and to better identify the ideal candidate for the procedure. Methods We included all consecutive female patients treated with urethral bulking with Bulkamid at our institution within 2 years. Patients were affected by stress urinary incontinence (SUI) or mixed incontinence. Incontinence severity was classified as “mild” (urinary leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 19 publications
3
24
2
1
Order By: Relevance
“…Twenty‐two percent of our patients had PAHG‐related postoperative urinary retention which followed complete spontaneous resolution within a few days of CIC. This was higher than in other studies that reported urinary retention rates of 5.7%, 23 1.1%, 9 1.9%, 7 13%, 15 or 8.2% 25 …”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Twenty‐two percent of our patients had PAHG‐related postoperative urinary retention which followed complete spontaneous resolution within a few days of CIC. This was higher than in other studies that reported urinary retention rates of 5.7%, 23 1.1%, 9 1.9%, 7 13%, 15 or 8.2% 25 …”
Section: Discussioncontrasting
confidence: 67%
“…This was higher than in other studies that reported urinary retention rates of 5.7%, 23 1.1%, 9 1.9%, 7 13%, 15 or 8.2%. 25 Mean PVR volume increase from baseline as a consequence of botulinum toxin injection were highest (+71 ml) at the 14-day visit, and decreased to +20 ml after 4 months. Other studies with 100 units of botulinum toxin reported similar kinetics, with a maximum increase after 2 weeks (+49.5 ml, 14 +50 ml, 24 +48.78 ml 19 ), and a decrease at 12 weeks (+32.6 ml, 14 +35 ml, 24 +15.53 ml 19 ).…”
Section: Postoperative Pvr Volumes Comparison To Other Studiesmentioning
confidence: 88%
“… 1 3 The most appealing features both for patients and clinicians are the extreme simplicity of the surgical procedure and the very low incidence of peri-operative and long-term complications, which include self-limiting hematuria, temporary urinary retention and uncomplicated urinary tract infections. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its relative inferiority in terms of clinical outcomes when compared to mid-urethral slings (MUS) was clearly stated by several works [ 1 , 2 ]. In fact, according to literature, the dry rate of UB can range from 16% to 50% despite a high satisfaction rate (up to 80% according to some studies) [ 2 , 3 , 4 ]. Furthermore, it is still not clearly stated whether functional results can be persistent over time or if the procedure needs to be repeated in order to maintain its efficacy since results from several studies are contradictory [ 5 ].…”
Section: Introductionmentioning
confidence: 99%